Analisis Pengaruh Store Atmosphere terhadap Minat Kunjung Kembali di Restoran Taman Santap Rumah Kayu Bandar Lampung - Subiyanto, Jennyfer Audry; Ritonga, Roozana Maria (Universitas Batanghari Jambi, 2024)
The atmosphere in a restaurant is not just a detail, but a key factor in building and maintaining customer loyalty. This research aims to determine the influence of restaurant atmosphere on customers' desire to return to Taman Makan Rumah Kayu in Bandar Lampung. Simple linear analysis method. The results of this research indicate that the restaurant atmosphere has a significant influence on customers' interest in returning. These findings confirm that the restaurant atmosphere not only influences customers' interest in returning, but also directly influences the level of customer satisfaction at Taman Santap Rumah Kayu in Bandar Lampung.